2020
DOI: 10.1158/0008-5472.can-19-2991
|View full text |Cite
|
Sign up to set email alerts
|

iNOS Regulates the Therapeutic Response of Pancreatic Cancer Cells to Radiotherapy

Abstract: and Aprea. He has patents on applications related to work on oncolytic viral therapy, alpha virus-based vaccine, neo antigen modeling, CD40, GITR, OX40, PD-1, and CTLA-4. Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Benkhelifa et al observed that significantly increased iNOS mRNA expression in metastatic tissues of colorectal cancer compared to primary tumors and unaffected mucosa [ 19 ]. Pereira et al showed that iNOS expressions were significantly increased in cancer-associated fibroblasts in pancreatic ductal adenocarcinoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benkhelifa et al observed that significantly increased iNOS mRNA expression in metastatic tissues of colorectal cancer compared to primary tumors and unaffected mucosa [ 19 ]. Pereira et al showed that iNOS expressions were significantly increased in cancer-associated fibroblasts in pancreatic ductal adenocarcinoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies indicate an influx in suppressive macrophages, Tregs and increases in inducible Nitic Oxide Synthase (iNOS) release by cancer-associated fibroblasts that together result in poor T-cell activity and sparse infiltration of pancreatic tumor tissues. [76][77][78] In contrast, chemotherapy is hypothesized to increase T-cell priming, which we discuss further briefly, and data from our group and others indeed suggest immune changes elicited by chemotherapy are significant. 76 79 Thus, considering how immunotherapy approaches can be strategically combined with radiation or chemotherapy will be key in moving forward.…”
Section: Therapeutic Approaches To Ameliorate T-cell Exclusion and Inmentioning
confidence: 77%
“…Similarly, in a model of pancreatic ductal adenocarcinoma, conditioned medium from irradiated fibroblasts (5 Gy) increases iNOS/NO signaling in cancer cells, activating the production of pro-inflammatory cytokines through NF-kB signaling. The activation of this pathway increases cancer cell aggressiveness, with higher cell growth, migration invasion and metastatic potential (118). CAFs promote cancer cell aggressiveness also by secreting factors that induce EMT.…”
Section: Fibroblasts and Mesenchymal Stem Cellsmentioning
confidence: 99%